Prosodie und Konstruktionsgrammatik - Imo, Wolfgang; Philipp Lanwer, Jens (Empirische Linguistik / Empirical Linguistics, 2020)
Most forms of construction grammar offer a usage-based model of grammar. To date, construction grammar researchers have been dismissive of prosody. This anthology seeks to redress this gap in the research, examining the extent to which prosodic characteristics may be viewed as more or less stable characteristics of linguistic constructions.